A novel HLA‐B allele, B*40:01:06, identified by sequence‐based typing in a Chinese individual. Issue 3 (10th February 2013) - Gong, Z.; Zhang, Z.; Shan, X.; Li, W.; Liu, N.
<x xml:space="preserve">Abstract</x> The sequence of HLA‐B*40:01:06 differs in exon 3 from the sequence of B*40:01:01 by one nucleotide 435 (codon121) G to A.